E-Commerce - Nguyen, Thi Hong Hanh (Khoa Quốc tế, ĐHQGHN, 2020)
This course provides students with the basic of Electronic commerce (EC), the models in EC, and online transactions. This course also provided students with techniques in applying EC tools, technologies, payment system and security in EC transaction. This course will also introduce to students about the EC promoting and E-Retailing.